The Role of Outside Director in Corporation with Significant Shareholders in Public Listed Companies on Pakistan Stock Exchange - Ullah, Ibad; Zia Ur Rahman; Muhammad Waseem (Journal of Business & Tourism, 2023)
This study investigates the role of the outside independent director and the effect of significant shareholders on firm performance. This study is based on quantitative research for which secondary data of Non-financial firms is collected from the PSX for 2007 to 2021. This study also investigates the effect of Firm size, Firm sales and Leverage on firm performance. The result shows that outside directors (ODR) affect positively the firm performance (TOBIN’S Q ). This can be since ODR are autonomous, master and well mindful of distinctive businesses whereas significant concentrated shareholders (SS) have a solid coordinate than the scattered shareholders. More the voting power of the concentrated shareholders has given them administrative control which works within the best intrigue of the owners.